Vertical wheel-rail force waveform identification using wavenumber domain method. (October 2021) - Liu, Qingjie; Lei, Xiaoyan; Rose, Jerry G.; Chen, Hua-Peng; Feng, Qingsong; Luo, Xinwei
Highlights: A wavenumber domain method is introduced. Wheel-rail force identification by using wayside monitor data. The regularization method is used solve the reverse problem. FE model is adopted to analyze the accuracy. Rail Corrugation is identified by WDM method. Abstract: Wheel-rail vertical force is the main cause of service performance degradation of both vehicle components and track structures. In this paper, a Wavenumber Domain Method (WDM) was developed for identifying vertical wheel-rail force waveform from monitoring data of rail dynamic responses. A one-layer track model is used to derive the transfer equation from wheel-rail vertical forces to rail dynamic responses i.e. strains, displacements. The transfer equations can be solved by the regularization method. The influence of measurement error and parameter estimate error are investigated. A vehicle-track coupled finite element (FE) model is adopted to analyze the accuracy of the method, and the result shows that the WDM provides the identification of wheel-rail force accurately. Serious field tests were conducted on a metro line. Results demonstrate the accuracy and applicability of the proposed approach to identify wheel-rail forces.